Development of the "Industrial Mandarin" MOOC for Practical Mandarin Language Learning in the Manufacturing and Technology Sectors - Galuh Bunga Usadani; Octi Rjeky Mardasari; Danang Yugo Pratomo; Renda Yuriananta; Dzun Nun Septin Renda Rabbani (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
The development of the manufacturing and technology sectors requires effective cross-cultural communication skills. Mandarin has become a strategic competency in the workplace due to the large number of companies that interact with partners or experts from China. However, Mandarin language learning at the higher education level in Indonesia still tends to be academic and does not fully accommodate the practical language needs of the industrial environment. This study aims to develop a Massive Open Online Course (MOOC) called "Industrial Mandarin" as an interactive online learning medium that is contextual to the world of manufacturing and technology. The study uses the 4D (Define, Design, Develop, Disseminate) Research and Development (R&D) model. Data was obtained through interviews with industry partners and questionnaires administered to 85 respondents working in the manufacturing sector. The results show that the Industrial Mandarin MOOC has a validity rate of 91% (highly valid) and a practicality rate of 89% (highly practical). The final product includes ten learning topics, two digital modules, and explanatory videos uploaded to mooc.um.ac.id.